The impact of carrying load on physical performance during ascending evacuation movement. (18th April 2020) - Velasco, Alejandra; Halder, Amitava; Kuklane, Kalev; Ronchi, Enrico
Summary: This study investigates how ascending movement is affected by carrying load during a stair‐climbing motion. The methods adopted are based on exercise physiology and fire safety engineering. Experiments with 21 volunteers with mean (SD) age of 27 (4) have been carried out on a stair machine with or without carrying a mass of 8 kg, typical weight of a hand luggage or the average weight of an 8‐months old infant. Oxygen uptake ( V˙ O2 ), heart rate (HR), metabolic rate (M), and perceived exertion results showed a decrease in performance in the scenario with additional load. Participants climbed an average of 92 m without carrying a load, in comparison to 84 m when they were carrying it in a 5 minutes task. An average increase of 4% in the V˙ O2 and the HR was found in the experiments with the additional mass. The strongest correlating variables observed were M and the vertical distance covered. Differences in perceived exertion occurred after four minutes into the exercise, with higher values in the case with additional load. These results show the need for considering the negative impact of carrying load while designing infrastructures in case of ascending evacuation and while developing evacuation modelling tools.